Oral Ibuprofen Induced Spontaneous Intestinal Perforation in a Preterm Infant - Şahin Hamilçıkan; Övgü Büke; Sultan Bent; Esra Özcan; Emrah Can (Galenos Yayinevi, 2017)
Ibuprofen is often used as an alternative for patent ductus arteriosus (PDA) management in preterm infants. The reported side effects are fewer than those of indomethacin. Spontaneous intestinal perforation differs from necrotizing enterocolitis, presents an early clinical picture and usually occurs after corticosteroid treatment in preterm infants. We present a case of a preterm neonate with spontaneous intestinal perforation induced by oral ibuprofen treatment for PDA.